Coordination chemistry and structural rearrangements of the Me2PCH2AlMe2 ambiphilic ligand. Issue 39 (16th September 2022) - Paskaruk, Katarina; Emslie, David J. H.; Britten, James F.
Abstract : Reactions between (Me2 PCH2 AlMe2 )2 and late transition metal complexes led to five distinct outcomes, ranging from Me2 PCH2 AlMe2 coordination to in situ generation of a tris(phosphino)aluminate ligand. Abstract : Reaction of 2 equivalents of (Me2 PCH2 AlMe2 )2 with [RhCl(cod)2 ] (cod = 1, 5-cyclooctadiene) afforded [κ 2 P, P -(Me3 Al)ClMeAl(CH2 PMe2 )2 Rh(cod)] (1 ), which features a κ 2 -coordinated bis(phosphino)aluminate anion. In compound 1, an Al–Cl substituent bridges to a molecule of AlMe3, which could be removed in vacuo to provide [κ 2 P, P -ClMeAl(CH2 PMe2 )2 Rh(cod)] (2 ). By contrast, reaction of 1 equiv. of (Me2 PCH2 AlMe2 )2 with [RhCl(cod)2 ] yielded [Rh(cod)(μ-Cl)(Me2 PCH2 AlMe2 )] (3 ) as the major product, where the phosphine donor of an intact Me2 PCH2 AlMe2 ligand is coordinated to rhodium and a chloride ligand bridges between Rh and Al. [Rh(cod)(μ-Cl)(Me2 PCH2 AlClMe)] (3A ) and 2 were also formed as minor products. The aforementioned reactions were carried out in benzene or toluene, whereas the 1 : 1 reaction of (Me2 PCH2 AlMe2 )2 with [RhCl(cod)2 ] in THF afforded [Rh(μ-CH2 PMe2 )(cod)2 ] (4 ). Reactions of (Me2 PCH2 AlMe2 )2 with iridium(i ), gold(i ) and platinum(ii ) precursors were also explored. A 1 : 1 reaction of (Me2 PCH2 AlMe2 )2 with [IrCl(cod)2 ] afforded [κ 2 P, P -Cl2 Al(CH2 PMe2 )2 Ir(cod)] (5 ) as one of two major phosphine-containing products; unlike 3, this compound features two chlorine substituents on aluminium. For comparison, the rhodium analogue of 5, [κ 2 P, P -Cl2 Al(CH2 PMe2 )2 Rh(cod)] (6 ), was also synthesized via the 1 : 1 reaction of ClAl(CH2 PMe2 )2 2 with [RhCl(cod)2 ]. Reactions of (Me2 PCH2 AlMe2 )2 with [AuCl(CO)] or [PtCl2 (cod)] also resulted in chloride–methyl group exchange between the transition metal and aluminium. However, these reactions generated free (Me2 PCH2 AlClMe)2 accompanied by gold and ethane, or [PtMe2 (cod)], respectively. Reaction of 1.5 equivalents of (Me2 PCH2 AlMe2 )2 with [PtMe2 (cod)] at 75 °C afforded zwitterionic [(PtMeμ-κ 1 P :κ 2 P, P -MeAl(CH2 PMe2 )3 )2 ] (7 ) which features two tris(phosphino)aluminate anions bridging between PtMe units. Compounds 1–2, 3 /3A, 4–7 and (Me2 PCH2 AlClMe)2 were crystallographically characterized.